The Impact of Soiling on Photovoltaic Performance in Iraq: Review - Rashak, Zahraa M.; Hassan, Kadhim H. (Basrah Journal for Engineering Sciences, 2024)
Solar power systems, also known as photovoltaic (PV) systems, are widely used as a clean and sustainable energy source worldwide. However, these systems can be affected by various factors that contribute to dust accumulation, which have been grouped into five categories: module characteristics, environmental factors, climatic conditions, exposure situations, and soiling properties. Dust accumulation can significantly impact photovoltaic modules’ efficiency and power output, leading to a decrease in electricity generation. Airborne dust reduces the intensity of solar radiation by scattering and absorbing it, especially in hot and dry regions such as southern Iraq. This study provides an updated overview of the process of dust accumulation on photovoltaic modules south of Iraq. Moreover, it illustrates the methods used to measure dust accumulation and the performance of solar PV under soiling. Furthermore, it exemplifies the sources of the soiling generation. Additionally, it demonstrates the composition and size of dust particles. Finally, future research perspectives are discussed, and a thorough investigation of the impact of dust is suggested in all regions of Iraq and even in all countries of the world, especially those interested in clean energy. This research aims to understand the effect of dust soiling on PV performance. The outcome of this research will help design the PV module system while considering the most effective method to reduce or prevent dust accumulation in specific areas.